2018
DOI: 10.1136/bmjopen-2017-018060
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and body adiposity among populations in Eastern Canada: the Atlantic Partnership for Tomorrow’s Health Study

Abstract: ObjectivesThe prevalence of obesity among populations in the Atlantic provinces is the highest in Canada. Some studies suggest that adequate fruit and vegetable consumption may help body weight management. We assessed the associations between fruit and vegetable intake with body adiposity among individuals who participated in the baseline survey of the Atlantic Partnership for Tomorrow’s Health (Atlantic PATH) cohort study.MethodsWe carried out a cross-sectional analysis among 26 340 individuals (7979 men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 31 publications
1
44
2
2
Order By: Relevance
“…Race, age [ 23 ], sex [ 24 ], and BMI [ 25 ] have been associated with dietary intake. Thus, in regression models, we controlled for these variable as potential confounders of the FCP-dietary intake relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Race, age [ 23 ], sex [ 24 ], and BMI [ 25 ] have been associated with dietary intake. Thus, in regression models, we controlled for these variable as potential confounders of the FCP-dietary intake relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the physical activity levels of participants were collected using open-ended questions in the International Physical Activity Questionnaire (IPAQ) [ 18 ]. For each participant, a total physical activity score in metabolic equivalents of a task (MET)-minutes per week was calculated according to the IPAQ scoring protocol and then sex-specific total MET scores were ranked into tertiles and levels of total physical activity were classified as low, medium and high by the MET score tertiles [ 19 , 20 ]. For smoking behaviour, participants were categorized as current smoker, former smoker or never smoked.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that high vegetable and fruit intake was inversely associated with body weight [ 36 , 37 , 38 ]. However, no association between vegetable intake and risk of overweight or obese was observed in other studies [ 34 , 39 , 40 ]. Higher adherence to the Prudent diet in the current study may not have a significant impact on overweight/obesity even though it was loaded with pulses, legumes, green leafy vegetables, cruciferous vegetables, other vegetables, root vegetables, starchy vegetables, mixed vegetables, vegetable soups, and fruits.…”
Section: Discussionmentioning
confidence: 73%